2021
DOI: 10.3390/challe12010003
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Spread of Infectious Diseases with Application to COVID-19

Abstract: Given the present pandemic caused by the severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2 virus, the authors tried fitting existing models for the daily loss of lives. Based on data reported by Worldometers on the initial stages (first wave) of the pandemic for countries acquiring the disease, the authors observed that the logarithmic rendering of their data hinted the response of a first-order process to a step function input, which may be modeled by a three-parameters function, as described in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Valvo et al, (2020) demonstrated that the Bimodal Lognormal Distribution, as a phenomenological epidemiological model, better predicts COVID-19 deaths [ 14 ]. Unglaub and Spendier (2021) fitted different sigmoidal distributions, primarily Gompertz, Richards, Logistic, Stannard, and Schnute, to analyze the infectious diseases dissemination with application to COVID-19 data, and found that the Richards model was fitted most suitable for the COVID-19 data because it had the lowest residual sum of squares[ 15 ]. Vazquez et al, (2021) worked on finding the best explaining distribution for the spread of the infectious diseases and for the study the author fitted the exponential, gamma and power-law distributions and shown their short-term and long-term behaviors for the infectious dissemination[ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Valvo et al, (2020) demonstrated that the Bimodal Lognormal Distribution, as a phenomenological epidemiological model, better predicts COVID-19 deaths [ 14 ]. Unglaub and Spendier (2021) fitted different sigmoidal distributions, primarily Gompertz, Richards, Logistic, Stannard, and Schnute, to analyze the infectious diseases dissemination with application to COVID-19 data, and found that the Richards model was fitted most suitable for the COVID-19 data because it had the lowest residual sum of squares[ 15 ]. Vazquez et al, (2021) worked on finding the best explaining distribution for the spread of the infectious diseases and for the study the author fitted the exponential, gamma and power-law distributions and shown their short-term and long-term behaviors for the infectious dissemination[ 16 ].…”
Section: Introductionmentioning
confidence: 99%